Mulheres de direita, imprensa e o golpe de 1964: a “marcha” noticiada: Right women, press and the 1964’s coup: the “march” notified (Revista de História da UEG (REVHIST), 2021)
In this article, I analyze the way in which the great Brazilian press reported on the March of the Family with God for Freedom, which took place on April 2, 1964, in the city of Rio Janeiro. To this end, I first cover the trajectory of the right wing women's groups created since 1962, especially the Women's Campaign for Democracy (CAMDE), and the relationships of these women's associations with some of the main vehicles of communication in Brazil. In a second moment, I check both the preparations for the "March", widely reported by the main newspapers in the country, and the way in which the public act was portrayed by the press. I understand that the women's groups acted in accordance with a large part of the press of the time, in mobilizations that collaborated in the formation of consensus around the destabilization and the fall of the João Goulart government.Keywords: Press. Rights. 1964’s coup.